# Solve for m 11m^2-2m=10 11m2-2m=10
Move 10 to the left side of the equation by subtracting it from both sides.
11m2-2m-10=0
Use the quadratic formula to find the solutions.
-b±b2-4(ac)2a
Substitute the values a=11, b=-2, and c=-10 into the quadratic formula and solve for m.
2±(-2)2-4⋅(11⋅-10)2⋅11
Simplify.
Simplify the numerator.
Raise -2 to the power of 2.
m=2±4-4⋅(11⋅-10)2⋅11
Multiply 11 by -10.
m=2±4-4⋅-1102⋅11
Multiply -4 by -110.
m=2±4+4402⋅11
Add 4 and 440.
m=2±4442⋅11
Rewrite 444 as 22⋅111.
Factor 4 out of 444.
m=2±4(111)2⋅11
Rewrite 4 as 22.
m=2±22⋅1112⋅11
m=2±22⋅1112⋅11
Pull terms out from under the radical.
m=2±21112⋅11
m=2±21112⋅11
Multiply 2 by 11.
m=2±211122
Simplify 2±211122.
m=1±11111
m=1±11111
The final answer is the combination of both solutions.
m=1+11111,1-11111
The result can be shown in multiple forms.
Exact Form:
m=1+11111,1-11111
Decimal Form:
m=1.04869579…,-0.86687761…
Solve for m 11m^2-2m=10

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top